Modeling signal telephone line using TLM - Pinho, Antonio C.; Muncinelli, Gianfranco (Visión electrónica, 2011)
The twisted pair media is still being used totransmit data as it is used to transmit voice.The effi ciency of the modem system ischallenged by the impairments of signalingsystem used by POTS (plain old telephoneservice). Those twisted pairs mean moneyand they will be used for a time. This paperpresents the use of the transmission line methodcombinated with Fourier analysis, aimingto refi ne the model of the twisted pair,in special way the use in data transmission.The effects of impairments such ringing,hook fl ash and dialing can be studied.